SMEs Internationalization Process through Brand Awareness and Perceived Quality - Sultoni, Mohammad Hamim; Sudarmiatin, Sudarmiatin; Bidin, Rosmiza (Journal of Economics Education and Entrepreneurship, 2022)
The development of technological knowledge of SMEs is increasing, and the dynamics in the global economy had a significant effect on SMEs. SMEs need to expand their market share to expand in international markets. This research examined the effects of brand awareness and perceived quality on the internationalization process of SMEs that were carried out on 367 SMEs in Madura. The research results indicated that the brand awareness variable had no significant effect on the internationalization process of SMEs. The significance value was more significant than 0.05, namely 0.079 > 0.05, and had a smaller tcount than ttable, namely 1.760 < 1.966. Meanwhile, the perceived quality variable had a significant effect on the internationalization process of SMEs because the significance value obtained was smaller than 0.05, namely 0.000 < 0.05, and had a greater tcount than ttable, namely 8.671 > 1.966. The variables of brand awareness and perceived quality simultaneously had a significant effect on the internationalization process of SMEs. Based on the results of the F-test on the comparison between Fcount > Ftable, the Fcount was 61.817, or more significant than Ftable, 3.01. The analysis results showed that the magnitude of the effects of brand awareness and perceived quality on the internationalization process of SMEs was only 24.9%. The remaining 75.1% might be affected by variables not mentioned in this research.